The Effect of Atorvastatin and Atorvastatin-Ezetimibe Combination Therapy on Androgen Production in Hyperandrogenic Women with Elevated Cholesterol Levels - Krysiak, R.; Okopien, B. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Statins decreased serum androgen levels in hyperandrogenemic women with polycystic ovary syndrome. No previous study has investigated whether this effect is dose-dependent and observed in patients simultaneously treated with other hypolipidemic agents. The study included 23 premenopausal women with elevated total testosterone levels coexisting with hypercholesterolemia, unsuccessfully treated for at least 6 months with atorvastatin (20 mg daily). These patients were then treated with either an increased dose of atorvastatin (40 mg daily, n=11) or atorvastatin (20 mg daily) plus ezetimibe (10 mg daily) (n=12). Plasma lipids, glucose homeostasis markers and serum levels of androgens, sex hormone-binding globulin and gonadotropins were assessed at baseline and after 3 months of treatment. Although both treatments decreased plasma levels of total and LDL-cholesterol levels, only high-dose atorvastatin reduced serum levels of total testosterone, free testosterone and androstendione. The effect of high-dose atorvastatin on serum androgen levels did not differ between insulin-resistant and insulin-sensitive subjects. The obtained results suggest that atorvastatin reduces serum androgen levels in a dose-dependent manner and that its administration in a higher dose is associated with a more pronounced effect on serum androgens than combination therapy with low-dose atorvastatin and ezetimibe.
Keywords: ezetimibe; hormones; hypercholesterolemia; insulin resistance; polycystic ovary syndrome; statins